USING DRAMA IN EFL CLASSROOM FOR EXPLORING STUDENTS’ KNOWLEDGE AND LEARNING - Deri Sis Nanda; Susanto Susanto (English Review: Journal of English Education, 2021)
This paper reported a research project on using drama in English as foreign language (EFL) classroom for exploring students’ knowledge and learning. The exploration aimed at understanding the students’ interests, abilities and motivations. Then, we also observed the teacher’s perceptions in the classrooms during the implementation of the drama for the students. In the study, we find that students show their good engagement and comprehension abilities. However, the perceptions of the teachers varied on the several aspects of the students’ preparation and performance. Further, their perceptions reflect the pedagogical context offering possibilities for cultural production in language learning. The research results underline how the drama can be used to construct the abilities for early language learners especially for social engagement and language comprehension.